Effects of nitrogen on corn and Brachiaria brizantha intercrops - Jakelaitis, Adriano (2008)
This work aimed at evaluating the effects of nitrogen (N) applied to topdressing on corn nutrient contents and yield, as well as intercropped Brachiaria brizantha biomass and mineral composition. Five N concentrations (0, 60, 120, 180, and 240 kg ha-1) applied to topdressing were evaluated, together with a corn sole crop control, fertilized with N at 120 kg per ha-1. Twenty days after corn emergence (DAE), the herbicides (nicosulfuron and atrazine) were applied in order to minimize the competition between the intercropped species, and fertilization as topdressing occurred at 25 DAE. Corn nitrogen, phosphorus, potassium, calcium, magnesium and chlorophyll contents were assessed, as well as one thousand kernels' yield and weight. B. brizantha biomass and mineral composition were measured at the corn harvest 50 days after harvest (DAC), and 40 days after B. brizantha graze period (DAP). An increase in chlorophyll and organic N contents, yield and weight of the thousand-corn-kernels sample was verified, proportional to the N doses increase. When the 120 kg ha-1 N proportion was applied in the sole crop and intercrop, no difference was observed among the characteristics. N doses increase engendered a larger forage production and organic N content in the B. brizantha shoots.